The type and incidence of adverse drug events in ageing medical inpatients and their effect on length of hospital stay. (24th February 2017) - Paradissis, Chariclia; Coombes, Ian D.; Donovan, Peter; Doran, Elizabeth; McKean, Mitchell; Barras, Michael A.
Abstract: Aims: To determine the proportion of older medical patients who have an adverse drug event (ADE) during admission to hospital and assess the association with hospital length of stay (LOS). Methods: A retrospective evaluation of eligible patients, aged greater than 65 years, consecutively admitted to a medical ward at the Royal Brisbane and Women's Hospital, Australia. Patient medication charts, medical notes and laboratory results were reviewed using an ADE trigger tool to identify potential ADEs during admission. A clinical panel examined and confirmed any true ADEs and the corresponding causative agents. LOS was compared between patients who did and did not have an ADE. Results: A total of 164 patients were recruited over 30 days. The trigger tool identified a total of 69 triggers from 40 patients (24.3%) with a potential ADE during admission, of which 12 patients (7.3%) had a true ADE. The main drug categories implicated included cardiovascular, anti‐infective and haematological agents. The group of patients with an ADE had a longer median (25th, 75th percentile) LOS when compared to patients without an ADE: 6.5 (3.75, 11) versus 4 (2, 7) days (p = 0.043). Conclusion: Approximately 7% of older in‐patients experience an ADE, which has a significant association with an increase in their LOS. To minimise patient harm, undesirable high‐risk drugs should be avoided and vigilant monitoring must occur if they need to be prescribed. An adequately powered, multi‐site study is required and preventative strategies should be further explored.